P056 Important role of CD11C+ dendritic cells in inflammatory arthritis. (21st February 2018) - Puchner, A; Saferding, V; Pfeifle, R; Krönke, G; Redlich, K; Smolen, J; Blüml, S
Abstract : Introduction: The main function of dendritic cells (DCs) is to present antigen to T-cells and therefore they play an important role in bridging the innate and the adaptive immune response. However, DCs can be divided in different subsets, which have intrinsic differences that lead to functional specialisation in the generation and maintenance of autoimmunity. Therefore the aim of our study was to investigate the role of CD11c + conventional DCs and monocytes dervived DCs in inflammatory arthritis. Methods: We analysed histological sections of K/BxN serum transfer arthritis as well as hTNFtg arthritis for the presence of CD11c + cells by immunohistochemistry. We also performed synovial biopsies and analysed the cellular composition of the inflammatory infiltrate with respect to DCs. We used CD11c-diphteria toxin receptor (DTR) transgenic mice, which express the human diphtheria-toxin receptor under the CD11c promoter, allowing for specific depletion of CD11c + cells by administration of diphtheria toxin (DT). K/BxN serum transfer arthritis was induced, and mice were given either DT or PBS or in wt and BARF3 deficient mice. In addition CD11c DTR mice were crossed into hTNFtg animals and also received either DT or PBS. The severity of arthritis was determined clinically and histologically. Results: We show that Cd11c + cells are present in significant numbers in the synovia of K/BxN and TNF driven arthritis. Both CD8 + CD11c + and CD11b + CD11c +, can be found in synovial tissue. In K/BxN serum transfer arthritis, clinical scores showed that CD11c-DTR transgenic mice that received DT had significantly reduced paw swelling and loss of grip strength compared to PBS treated animals. Histological analysis found reduced inflammation after the depletion of CD11c + cells in K/BxN arthritis. In addition local bone destruction and the number of osteoclasts was significantly reduced. Analysis of K/BxN arthritis in wt mice and BATF3 -/- mice, which lack CD8 + CD11 + DCs revealed no difference in arthritis severity between the two groups. In addition to K/BxN arthritis, we found that also in TNF-driven arthritis depletion of CD11c + cells led to a significant reduction of synovial inflammation and a complete depletion of osteoclasts. Conclusions: These data show that in addition to initiating an adaptive immune response, CD11c + dendritic cells, are also involved in innate effector mechanisms of inflammatory arthritis. Especially CD11b + CD11c + and monocyte derived inflammatory seem to play a role in inflammatory arthritis, suggesting that they could be an important therapeutic target for patients suffering from inflammatory arthritis. Disclosure of interest: None declared